Exercises with action observation contribute to upper limb recovery in chronic stroke patients: a controlled clinical trial - Angela Cristina de Lima; Gustavo Christofoletti (Universidade Estadual Paulista (UNESP), 2020)
Abstract Aims: To investigate the effects of an exercise program with action observation versus conventional physical therapy on upper limb functionality in chronic stroke subjects. Methods: In this controlled clinical trial, thirty-five stroke patients were divided into two groups, experimental group, comprising eighteen patients that received an exercise program with action observation; and a control group, comprising seventeen patients that received conventional exercise program. Functional recovery was assessed with the Fugl-Meyer Scale, manual dexterity was assessed with the Box and Blocks test, and the functional use of the affected upper limb was assessed with the Reach scale. Evaluations occurred at baseline, after three and six months of intervention. Statistical analyses were performed with the Repeated Measures Analysis of Variance and the Friedman test, under a 5% significance. Results: Both interventions provided benefits to chronic stroke patients. Exercise program with action observation presented better results on motor recovery (p < 0.001) and functional use of the affected limb (p < 0.001) when compared with conventional therapy. Both treatments improved the manual dexterity of the participants (p = 0.002), but in a similar way (p = 0.461). Conclusion: A six-month exercise program with action observation provided benefits on functional recovery and functional use of an affected upper limb in chronic stroke patients. Exercises with action observation demonstrated the potential for improving affected upper limb in chronic stroke patients.